2023
DOI: 10.3390/ijms24087579
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Disruption and Mental Health: The Chronotherapeutic Potential of Microbiome-Based and Dietary Strategies

Abstract: Mental illness is alarmingly on the rise, and circadian disruptions linked to a modern lifestyle may largely explain this trend. Impaired circadian rhythms are associated with mental disorders. The evening chronotype, which is linked to circadian misalignment, is a risk factor for severe psychiatric symptoms and psychiatric metabolic comorbidities. Resynchronization of circadian rhythms commonly improves psychiatric symptoms. Furthermore, evidence indicates that preventing circadian misalignment may help reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 143 publications
0
11
0
Order By: Relevance
“…Another 30-day longitudinal study on Chinese seafarers revealed that probiotics were able to maintain the homeostasis of the GM during a long sea voyage. The probiotics used in the study included strains such as Lactobacillus casei, Lactobacillus plantarum, L. rhamnosus, and B. lactis, which demonstrated excellent probiotic properties in previous studies [68,100].…”
Section: Use Of Probiotics To Restore Dysbiosis In Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 30-day longitudinal study on Chinese seafarers revealed that probiotics were able to maintain the homeostasis of the GM during a long sea voyage. The probiotics used in the study included strains such as Lactobacillus casei, Lactobacillus plantarum, L. rhamnosus, and B. lactis, which demonstrated excellent probiotic properties in previous studies [68,100].…”
Section: Use Of Probiotics To Restore Dysbiosis In Workersmentioning
confidence: 99%
“…Another option to reduce anxiety or depression would also be the supplementation of SCFA or dietary fiber intake [41], as recent research indicates that SCFA or the microbiota may influence brain function, such as anxiety or depression [100]. Therefore, it is possible that microbiota-derived metabolites reach the brain, and future studies are required to understand the impact of chronic SCFA administration on the circadian clock system in the brain [41].…”
Section: Use Of Probiotics To Restore Dysbiosis In Workersmentioning
confidence: 99%
“…The impact of circadian rhythm disruption extends to mental health, contributing to various psychiatric and neurological consequences. Disrupted sleep patterns are commonly observed in individuals with conditions such as major depressive disorder, bipolar disorder, anxiety, schizophrenia, autism spectrum disorders, and attention deficit hyperactivity disorder [19,20]. Understanding the intricate relationships between circadian rhythms, sleep, and health outcomes is crucial for developing comprehensive strategies to promote overall well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted sleep also significantly impacts mental health and is associated with multiple psychiatric as well as neurological consequences. Impaired circadian rhythms are commonly observed among individuals with various psychiatric disorders, including major depressive disorder, bipolar disorder, anxiety, schizophrenia, autism spectrum disorders, and attention deficit hyperactivity disorder [19,20]. Xu S et al (2021) explore the impact of circadian rhythms on diverse cognitive functions.…”
Section: Relationship Of Human Health Associated With the Circadian R...mentioning
confidence: 99%
“…Chrononutrition is a field of research in nutritional sciences that investigates the health impact of three different dimensions of feeding behavior: regularity of meals, frequency, and timing of food intake [ 1 ]. These are distinguished into early chronotypes and late chronotypes.…”
Section: Introductionmentioning
confidence: 99%